COMPARATIVE ANATOMICAL AND HISTOLOGICAL STUDY OF THE RABBITS (Oryctolagus cuniculus) ADRENAL GLAND AT THIRTY AND NINETY DAYS AGE - Hussein, Ahmed Abdulla; Abass, Thamir Abood (Diyala Agricultural Sciences Journal, 2015)
Twelve animals regardless of the sex divided equally into two age periods (30, 90 days age). The adrenal glands were collected and fixed in 10% neutral buffered formalin for cortical tissue and Orth’s solution for medullary tissue. These specimens were conducted for histomorphologic investigation applied in both age periods. The glands of rabbits were paired white to creamy in color, oval to crescentic in shape. It was embedded in fatty tissue, lying cranial to the cranial pole of kidney within the retroperitoneal cavity similar to these of other mammals. The left adrenal gland was far off from the left kidney as a compared with the right gland. Histological part included fixation of the adrenal glands and then processed by routine paraffin embedding. The sections of 6 μm thicknesses were stained by H&E, PAS and Van Gieson stains. The adrenal capsule observed as one layer in the two age periods. The zona glomerulosa appeared as arches of cells at sub capsular region, while the zona fasiculata and reticular zone were developed with age. Medulla composed of central vein surrounding by chromaffin cells.